Running Title: Gluten-Free Biscuit for Autism Children Gluten-Free Biscuit for Children with Autism Spectrum Disorder Made from Modified Taro Flour and Coconut Pulp Flour - Hamka, Hamka; Aryani, Farida; Darmans, Silvia; Rindawati, Rindawati; Warman, Dicky Aditya (Riviera Publishing, 2024)
Autism spectrum disorder (ASD) is common in children, many of whom require a gluten-free diet. This study explored gluten-free biscuits made with modified taro flour and coconut pulp flour, which are rich in carbohydrates, fats, fiber, and protein. The goal was to assess the physical, sensory, and chemical properties of biscuits made with different ratios of these flours. The research used four formulations of taro flour to coconut pulp flour: P0 (100:0), P1 (70:30), P2 (50:50), and P3 (30:70), with five replications. Data were analyzed using ANOVA and the Duncan Multiple Range Test (DMRT) at a 5% significance level. Results showed that the P2 (50:50) formulation produced the heaviest biscuits (5.32g) and scored highest in color (3.82) and taste (3.78) in sensory tests. The P3 (30:70) formulation was rated best for aroma (3.56) and texture (3.82). Chemical analysis revealed that P0 (100:0) had the highest water (1.85%), ash (2.22%), and carbohydrate content (61.32%). The P2 (50:50) formulation had the highest protein content (4.42%), while P3 (30:70) had the most fat (49.03%) and fiber (7.96%). This study concluded that modified taro flour and coconut pulp flour are effective in creating nutritious, gluten-free biscuits, offering a suitable alternative for children with ASD.